A new approach to the forensic classification of fraud (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article substantiates the need to develop a methodology for investigating fraud based on the forensic classification of these criminal offences. It is advisable to choose the criteria for classification of a particular type or group of crimes from the point of view of the practical significance of the differentiation made. Such a criterion ensures grouping of manifestations of crimes based on common features of the mechanism of commission, which, in turn, affects the formation of typical investigative situations of the initial and subsequent stages of investigation, tactical tasks and their solution by appropriate means. The analysis of works by forensic scientists and criminologists who propose to divide frauds into groups depending on the field of activity in which they are committed is made.It is determined that the methodology for investigating fraud developed on the basis of such a classification will not cover all types of crime, since there are many areas of human activity and each of them may implement fundamentally different schemes of fraudulent activity. Therefore, a different scientific approach to the forensic classification of fraud should be applied.It is noted that the classification should be carried out on the basis of certain elements of the mechanism of committing such criminal offences which significantly affect the formation of investigative situations, tactical tasks of investigation and means of their solution.The article emphasises that it is advisable to classify frauds by such a criterion as the type of legal relations used to implement a fraud scheme for seizing the victim's property or his/her property rights. According to this criterion, criminal offences are classified into: 1) frauds committed under the guise of civil legal relations and domestic transactions; 2) frauds committed under the guise of administrative legal relations; 3) frauds committed under the guise of economic legal relations.
Keywords: fraud; investigation methodology; fraud investigation; forensic classification of fraud; legal relations.